876 Burden associated with Fabry Disease and its treatment in 12- to 15-year-olds: results from an international survey. (17th August 2022) - McCaughey, Gerard; MacCulloch, Alasdair; Bashorum, Lisa; Evans, Owen; Humphries, Ashley C; Perry, Richard
Abstract : Aims: Fabry disease (FD) is an X-linked, multisystemic disorder caused by GLA variants resulting in α-galactosidase A deficiency. Patients with FD experience a wide range of symptoms, including hypo/hyperhidrosis, pain, and skin, digestive, renal and cardiac complications, which can arise in patients as young as 2 years old and manifest differently in each individual. This makes diagnosis and treatment challenging for healthcare professionals (HCPs). There is limited published research on the effects of FD on the adolescent patient population and their caregivers. The aim of this study was to collate the adolescent patient, caregiver and specialist HCP perspectives to improve understanding of the burden of FD and current treatment options in this patient population. Methods: In this non-interventional study, primary data were collected through online surveys from patients 12-15 years old diagnosed with FD and eligible for disease-specific treatment, their caregivers, and specialist HCP physicians. Survey data were collected anonymously. Questions in the surveys comprised rating statements and multiple-choice options designed to capture each stakeholder's perspective on the burden of FD and their experience of treatment. Additional comparative analyses were conducted on specific questions by Likert scoring. Results: A total of 14 patients (8 male; the majority [85.7%] aged ≤10 years at diagnosis), 14 caregivers and 5 specialist HCPs across France, Germany and the UK were surveyed. Within the adolescent population, symptom burden was high, with 'burning in the hands and feet', 'sweating less than normal' and 'sensitive to heat or cold' most commonly reported. Eleven patients (78.6%) were receiving enzyme replacement therapy (ERT), 1 was receiving vitamin D and ramipril for FD, 2 female patients were not receiving any disease-specific therapy. In ERT-treated patients, 14 symptoms showed improvement with ERT compared with symptom frequency before ERT, with 'stomach bloating and pain' and 'tiredness not relieved by sleep' displaying the greatest improvement; modest changes (1-2-point decreases) were reported for the majority of other symptoms ( figure 1 ). All respondents were on additional medications. Overall, patients had a positive outlook on treatment; of the 11 ERT-treated patients, 6 scored the statement 'I feel better since I started treatment' highly, and 5 scored 'I feel that treatment helps reduce my pain' highly. Burden of FD was also noted by caregivers; 9/14 (64.3%) caregivers reported 'sometimes' missing work, and on average, high agreement scores were reported for the statements 'I often feel guilty and wish I could do more to support my child' and 'due to my caregiver responsibilities, I struggle to balance work, family and find time for myself'. Most HCPs believed a key challenge in the treatment of FD was the impact of ERT on quality of life and its perceived lack of efficacy ( figure 2 ). Conclusion: Findings from this survey indicate a high symptom burden of FD in adolescents, which also places burden on their caregivers. While current treatments help to alleviate symptoms, disease burden remained high post-treatment. There is a need for additional FD treatment options which are more manageable and have less impact on adolescent quality of life. Supported by Amicus Therapeutics.